Dendritic cell-derived exosomes induce monocyte antigen-presentation and immune amplification in neoantigen vaccine therapy - Morisaki, Shinji; Onishi, Hideya; Morisaki, Takafumi; Kubo, Makoto; Umebayashi, Masayo; Tanaka, Hiroto; Koya, Norihiro; Nakagawa, Shinichiro; Tsujimura, Kenta; Yoshimura, Sachiko; Yew, Poh Yin; Kiyotani, Kazuma; et al. (Frontiers in Immunology, 2025)
Mature dendritic cells release exosomes; however, the immunological role of exosomes in dendritic cell vaccine therapy remains unclear. We examined the immunogenicity of neoantigen peptide-pulsed dendritic cell-derived exosomes (Neo-P DEX) and investigated their role in vaccine therapy. The quality of DEX derived from dendritic cell cultures was confirmed via electron microscopy, western blotting, flow cytometry, and CD63 ELISA. When DEX released from neoantigen-pulsed DCs was applied to monocytes, they showed dendritic cell-like properties such as surface antigen expression. Furthermore, monocytes receiving Neo-P DEX activated neoantigen-reactive T lymphocytes. Fluorescence-activated cell sorting (FACS) analysis showed that plasma exosomes after neoantigen-pulsed DC vaccine may contain more DEX compared to before the vaccine, suggesting that DEX released after DC vaccination may be involved in the amplification of tumor-specific immune responses by translocating to monocytes in the patient body and transforming them into antigen-presenting dendritic cells. This study suggests that dendritic cell exosomes may act as endogenous neoantigen vaccines or immune amplifiers.